2003
DOI: 10.1007/b11992
|View full text |Cite
|
Sign up to set email alerts
|

Power Units for Transportation

Abstract: This chapter reviews the environmentally relevant physical-chemical properties, partitioning and reactivity properties of a selection of organobromine and organoiodine compounds. Substitution of hydrogens with bromine or iodine is shown to cause significant changes in vapor pressure, solubility in water, and hydrophobicity (octanol-water partition coefficient). These property changes are similar to those caused by Substitution of hydrogen with chlorine, although there are quantitative differences attributable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…1a, or 3.7 km from the WTP outfall). Conventional wastewater treatment often consists of several phases: primary treatment (sedimentation), secondary treatment (biological) and at times a tertiary treatment (physico-chemical) to remove phosphorus and nitrate (Daughton and Ternes 1999). Numerous studies have shown that many micropollutants are often not eliminated by conventional WTPs (Daughton and Ternes 1999) and recent investigations at the Vidy WTP confirm that its effluent contains low concentrations of micropollutants such as pharmaceuticals (Margot et al 2013).…”
Section: Study Sitementioning
confidence: 99%
“…1a, or 3.7 km from the WTP outfall). Conventional wastewater treatment often consists of several phases: primary treatment (sedimentation), secondary treatment (biological) and at times a tertiary treatment (physico-chemical) to remove phosphorus and nitrate (Daughton and Ternes 1999). Numerous studies have shown that many micropollutants are often not eliminated by conventional WTPs (Daughton and Ternes 1999) and recent investigations at the Vidy WTP confirm that its effluent contains low concentrations of micropollutants such as pharmaceuticals (Margot et al 2013).…”
Section: Study Sitementioning
confidence: 99%